Chemical Analysis of the Indigenous drug: Sufoof-e-Mohazzil - balasubramanian, N.; Saravanan, D.; Jafar Ahamed, A. (Asian Journal of Chemistry, 2010)
Modern medicine cures diseases, but also causes side-effects and such side-effects are not observed much in the use of Siddha, Unani, Ayurveda and Homeophathy drugs. Very little work has been done regarding the systematic chemical analyses of Sufoof-e-Mohazzil indigenous drug.